Prevalence of Dental Hard Tissue Diseases Before and During the Pandemic in South Sumatera Dental Hospital - Nesha Dini Fania Putri; Danica Anastasia; Rinda Yulianti (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2023)
Introduction: The most common dental problems in Indonesia are broken/cavities/toothache. Dental hard tissue disease is one of the ten biggest outpatient diseases in South Sumatera Dental Hospital. The dental practice has been limited since the COVID-19 pandemic occurred. The frequency of permanent dental hard tissue disease cases at South Sumatera Dental Hospital has increased due to limited treatment access. Purpose: This study aims to find out the prevalence of permanent dental hard tissue disease before and during the pandemic at South Sumatera Dental Hospital. Methods: This study was a descriptive observational study with a cross-sectional design. Data were collected using the total sampling method, a medical record data on SIMRS BPJS application with a diagnosis of dental hard tissue disease at South Sumatera Dental Hospital. Results: The prevalence of dental hard tissue disease before and during the pandemic at South Sumatera Dental Hospital has decreased with the number before the pandemic being 2380 cases and during the pandemic was 770 cases. Conclusion: The prevalence of dental hard tissue disease at South Sumatera Dental Hospital has decreased during the pandemic. It is because the number of visits to health facilities has decreased due to the risk of spreading COVID-19 infection.